2017
DOI: 10.17221/141/2016-pse
|View full text |Cite
|
Sign up to set email alerts
|

Chemical properties and microbial responses to biochar and compost amendments in the soil under continuous watermelon cropping

Abstract: Biochar added to soil can improve crop growth and productivity. However, the mechanisms of crop growth improvement by biochar application are not well understood, particularly in the presence of soil-borne pathogens caused by continuous monocropping. Thus, a two-year field experiment was carried out to study the chemical and microbiological response of Lixisols (pH 5.8) to the amendment of biochar and its effect on watermelon productivity and Fusarium wilt disease incidence. Biochar was added alone or together… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…It is also one of the most important biochemical indicators for plants [28]. During this study, a rapid increase of chlorophyll was observed at the early growing stage (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). The chlorophyll content of rice subjected to the compost treatment was significantly higher followed, by those plants applied with biochar and GML.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…It is also one of the most important biochemical indicators for plants [28]. During this study, a rapid increase of chlorophyll was observed at the early growing stage (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). The chlorophyll content of rice subjected to the compost treatment was significantly higher followed, by those plants applied with biochar and GML.…”
Section: Discussionmentioning
confidence: 57%
“…The chlorophyll content of rice subjected to the compost treatment was significantly higher followed, by those plants applied with biochar and GML. This significant increase may be due to the improvement of the nutritional condition of soil, which can reflect the growth of the plant and the chlorophyll content [6,29].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the hydrolytic activity of the FDA is considered as an indicator of total microbial activity. The FDA hydrolytic activity was shown to be increased by biochar addition in a pot experiment [15], whereas no effect was found in a field study [33]. Another extracellular enzyme, protease, catalyzes the hydrolysis of the protein components in the N mineralization process, especially in the initial stage [34].…”
Section: Introductionmentioning
confidence: 98%
“…This parameter reflects the activity of several enzymes, such as lipases, esterases, and proteases (Araujo et al, 2015) and is considered by Adam and Duncan (2001) to be directly proportional to the bacterial population. Since metal(loid)s have a negative impact on several enzymes (Yun, Yan, Dejie, Qiujun, & Guangfei, 2017), the increase in FDA hydrolysis activities with RM2 can indicate a reduced metal(loid) toxicity in this treatment, which coincides with an improvement of the physicochemical soil conditions (increase in pH and nutrient availability, and decrease in soil pore water Pb concentration and availability) (Table S1; Lebrun et al, 2020). However, other treatments also revealed an improvement of these physicochemical conditions, at similar levels as RM2 in some cases, but these were not coinciding with an improvement of the global microbial activity assessed by FDA hydrolysis.…”
Section: Soil Enzyme Activitiesmentioning
confidence: 99%